Extension approaches to rice integrated pest management in the Philippines - Velasco, Luis Rey I. (1999)
The conceptual framework and field impact of the farmer field school (FFS) approach and the farmer participatory research (FPR) approach to integrated pest management (IPM) extension in the Philippines were reviewed. Published reports indicated the significant impact of the two participatory approaches in improving farmers' pest management decision making and practices, at least, in terms of reduction in pesticide use without significant yield reduction. Available published field data, however, were insufficient to critically examine the soundness of the conceptual frameworks of the two approaches and their underlying assumptions particularly in the context of farmer education.

The understanding of and skills in information evaluation through scientific experimentation, and appreciation of the underlying agroecological principles by farmers need to be measured. This is critical to improving theories and methods to help us better understand how to use the participatory approach more effectively in dynamic socio-cultural settings. Emerging issues were also discussed as questions of depth versus breadth and challenges were raised in translating theory into practice.
Keywords: Integrated Pest Management Farmers' Field School; Rice farmers; Farmers -- Philippines